The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/nhs.12936
|View full text |Cite
|
Sign up to set email alerts
|

Practices and experiences of European frontline nurses under the shadow of COVID‐19

Abstract: The COVID‐19 pandemic has caused health professionals to deal with new situations they have not encountered before. Nurses were forced to cope with increased workloads, seriously ill patients, numerous patient deaths, and unresolved ethical dilemmas. This study aimed to examine the lived experiences of nurses across Europe during the first wave of the COVID‐19 pandemic. This was a qualitative narrative research study. Eighteen nurses from eight European countries (four each from the UK and Israel, three from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Yet, ICUs were conceived for patient survival. In previous pandemics, such as MERS-CoV, studies reveal that nurses struggled with the ethical conflict of an evident patient-avoidance mentality in their efforts to dodge infection; however, during COVID-19, having to witness patients' loneliness at the time of death-as reported by several authors (Fernández-Castillo et al, 2020;Melnikov et al, 2022;Moore et al, 2022;Sezgin et al, 2021;Shin & Yoo, 2022)-is revealed as the main factor of ethical stress, given that it comes into conflict with a healthcare worker's responsibility to accompany their patients and to alleviate their suffering. Similarly, albeit to a lesser extent, was the suffering reported by some nurses during the first wave on having to provide post-mortem care-to-date an issue that has received little attention-and which raises the need to train professionals in these disciplines as part of their university education.…”
Section: Need To Humanise Carementioning
confidence: 99%
“…Yet, ICUs were conceived for patient survival. In previous pandemics, such as MERS-CoV, studies reveal that nurses struggled with the ethical conflict of an evident patient-avoidance mentality in their efforts to dodge infection; however, during COVID-19, having to witness patients' loneliness at the time of death-as reported by several authors (Fernández-Castillo et al, 2020;Melnikov et al, 2022;Moore et al, 2022;Sezgin et al, 2021;Shin & Yoo, 2022)-is revealed as the main factor of ethical stress, given that it comes into conflict with a healthcare worker's responsibility to accompany their patients and to alleviate their suffering. Similarly, albeit to a lesser extent, was the suffering reported by some nurses during the first wave on having to provide post-mortem care-to-date an issue that has received little attention-and which raises the need to train professionals in these disciplines as part of their university education.…”
Section: Need To Humanise Carementioning
confidence: 99%
“…As the COVID-19 pandemic intensified, there was an urgent need for an in-depth understanding of nurses’ lived experiences and their fear, moral distress, and challenges they experienced when caring for COVID-19 patients. Since the beginning of the pandemic, many studies have explored nurses’ experiences of care of COVID-19 patients in different healthcare settings, including intensive care units ( Brockopp et al, 2021 ; Gunawan et al., 2021 ; Karimi et al, 2020 ; N. Lee & Lee, 2020 ; H. Lee et al, 2022 ; Melnikov et al, 2022 ; Ménard et al, 2022 ; Moore et al, 2022 ; Moradi et al, 2021 ; Perraud et al., 2022 ; Robinson & Stinson, 2021 ) . These studies were conducted in North America (USA, Canada), Europe (Sweden, Italy, France), and Asia (Chania, South Korea, Iran).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, where healthcare systems were overwhelmed by rapid increases in the number of hospitalized patients, frontline healthcare workers continued to provide services. Their working environments were often very challenging, and many endured long work hours, anxiety and fear of infection, deficiencies in communication with middle management, and enormous stress (Barello et al, 2020; Fiabane et al, 2021; Melnikov et al, 2022). Accordingly, the pandemic's impact on healthcare workers, including nurses, and their mental health has attracted attention and many researchers have published reports on this topic (Al Maqbali & Al Khadhuri, 2021; De Kock et al, 2021; Ness et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…and many endured long work hours, anxiety and fear of infection, deficiencies in communication with middle management, and enormous stress (Barello et al, 2020;Fiabane et al, 2021;Melnikov et al, 2022).…”
mentioning
confidence: 99%